A comparative analysis of photocatalytic activity against methyl orange with C18 derivatives of fatty acid coated Ag/Ag-Ag2O nanoparticles. (2021) - Hasan, Shazia; Rauf, Abdul
Abstract: Even though the photocatalytic methods are better scientific tool for treating hazardous organic contaminants, most of the current photocatalysts are unable to employ sunlight adequately to degrade these pollutants. As reported by various researchers, metal oxide nanoparticles exhibit a substantial photocatlaytic performance under visible radiation source. With this regard, the C18 fatty acids capped Ag/Ag-Ag2 O nanoparticles are prepared through a facile and economic friendly chemical method. The structure, crystallinity, size and optical properties of synthesized nanoparticles were characterized by various techniques, like XRD, TEM, XPS; etc. The fine spherical distribution of nanoparticles capped with various fatty acids was confirmed by TEM while crystalline patterns were shown by XRD arrangement. The photocatalytic studies of modified silver nanoparticles have been discussed through the degradation of methyl orange dye under visible light irradiation. The results were in favour with the saturated chain of attached fatty acids with higher degradation percentage compared to the rest of the derivatives. Further the kinetic studies were explained for confirming the outcomes. The photocatalytic observation suggests the fatty acid coated Ag/Ag-Ag2 O nanoparticles can be implied as a competent in wastewater treatment.